The Efficacy of Planned Intervention on Maternal Stress in Malaysia's NICU - Ong, Swee Leong; Lim, Khatijah; Soh, Kim Lam; Soh, Kim Geok; Emni, Hussin (2019)
To evaluate the effectiveness of Planned Intervention (PI) in reducing maternal stress among Malay mother who has premature infant admitted to NICU.